Pemahaman Masyarakat Mengenai Pengelolaan Sampah Rumah Tangga di RT 03 RW 17 Kelurahan Kahuripan - Analiana, Shinta; Aisyi, Sarah Rohadatul; Putri, Nadia; Rahmayanti, Adisti Aisyah; Putri, Nadhifa Nuraini; Nurlaila, Nurlaila (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Waste management is one of the social problems that must be handled as soon as possible by the entire community. If waste management is not handled as early as possible, it will have a bad impact on life in the future. The pattern of consumptive community habits also affects the volume of waste produced. The purpose of this study is to find out the community's understanding of household waste management in RT 03 RW 17 Kahuripan Village. This study is a quantitative descriptive research using a questionnaire distribution that contains statements with multiple choices in the form of true and false. The overall research results are included in the high category (very good understanding) with a percentage of 65%. When viewed from the overall average value, the percentage is 80%. The highest percentage based on per indicator and per statement lies in the indicator summarizing precisely number 9 regarding the 3R principle and explaining, precisely in statement number 15 regarding waste disposal sites that must be adjusted to the type of waste with a percentage of 94.9%.